Internet of Things (IoT), challenges and perspectives in Romania: A qualitative research - Silviu-Gabriel Szentesi; Lavinia Denisia Cuc; Ramona Lile; Paul Nichita Cuc (Amfiteatru Economic Journal, 2021)
One may notice that there is a lack at a national level of studies providing scientific answers to problems such as: data safety, security and confidentiality of the data, economic viability, and impact, regarding internet interconnection of devices and equipment called the Internet of objects, and in English the Internet of Things. The implementation in industry, transportation and related services of the Internet of Things system is relatively new, being known and developed by Romanian companies more in the last five years, according to our study. The scientific research carried out was based on the semi-structured interview method, recorded audio and video through the Zoom interface. Data processing of was carried out by statistical methods advanced in the R program. The data obtained within the study provides relevant information at the level of users in the analysed fields based on a qualitative research and allows the creation of a first impression on the state of the implementation of the Internet of Objects in Romania, which represents the basis for the initiation of more focused quantitative research on all the implications of the development and use of the interconnection of devices via the Internet or other interconnection access systems.
Keywords: O14; 330; internet of things (IoT); industrial internet (IIoT); semi-structured interview; perceived risks; hypotheses; IoT perspectives